Pengaruh Compensation, Work Environment Terhadap Employee Performance Dimediasi Job Satisfaction Pada Industri Property - Hari Setianto, Rizky; Wahyu Gunawan. P, Andreas (Journal of Comprehensive Science, 2023)
This study aims to analyze the effect of Compensation, Work Environment on Employee Performance mediated by Job Satisfaction in the Property Industry. Where the research results prove that the Compensation variable is not supported to have an influence on Employee Performance. Job satisfaction in this study serves as a mediating variable for the influence of the Work Environment on Employee Performance. Furthermore Job satisfaction mediates the influence between job autonomy and employee performance. Companies that are used as samples in this study are companies engaged in the property industry. From the research results it can be seen that compensation has a positive and significant effect on job satisfaction and an indirect effect on employee performance through job satisfaction. The work environment variable from the research results is proven to have an influence on employee performance and job satisfaction. Job satisfaction has an influence on employee performance and can also mediate the effect of compensation, work environment and also job autonomy on employee performance. This research was conducted on 200 employees who work in companies engaged in the property industry. The analysis used in this research is SEM (Structural Equation Model) analysis.